The Broad-Scale Analysis of Metals, Trace Elements, Organochlorine Pesticides and Polycyclic Aromatic Hydrocarbons in Wetlands Along an Urban Gradient, and the Use of a High Trophic Snake as a Bioindicator - Lettoof, Damian C.; Bateman, Bill; Aubret, F.; Gagnon, Marthe Monique (SPRINGER, 2020)
Wetlands and their biodiversity are constantly threatened by contaminant pollution from urbanisation. Despite evidence suggesting that snakes are good bioindicators of environmental health, the bioaccumulation of contaminants in reptiles is poorly researched in Australia. We conducted the first broad-scale analysis of 17 metals and trace elements, 21 organochlorine pesticides, and 14 polycyclic aromatic hydrocarbons in the sediments (4 samples per site, December 2018) from four wetlands along an urban gradient in Perth, Western Australia, and from the livers (5 livers per site, February–April 2019) of western tiger snakes Notechis scutatus occidentalis captured at those sites. All 17 metals and trace elements were detected in the sediments of wetlands as well as 16 in the livers of tiger snakes. Arsenic, Cu, Hg, Pb, Se, and Zn were at concentrations exceeding government trigger values in at least one sediment sample. Two organochlorine pesticides and six of seven polycyclic aromatic hydrocarbons were detected in the sediments of a single wetland, all exceeding government trigger values, but were not detected in tiger snakes. Metals and trace elements were generally in higher concentration in sediments and snake livers from more heavily urbanised wetlands. The least urbanised site had some higher concentrations of metals and trace elements, possibly due to agriculture contaminated groundwater. Concentrations of nine metals and trace elements in snake livers were statistically different between sites. Arsenic, Cd, Co, Hg, Mo, Sb, and Se near paralleled the pattern of contamination measured in the wetland sediments; this supports the use of high trophic wetland snakes, such as tiger snakes, as bioindicators of wetland contamination. Contamination sources and impacts on these wetland ecosystems and tiger snakes are discussed herein.